NOMADIC, MIGRATING, COMMUTING, WEARABLE TECHNOLOGIES AND THEIR INFRASTRUCTURES - Tincuta HEINZEL; Lasse SCHERFFIG (Studia Universitatis Babeș-Bolyai. Philosophia)
One of the central issues of the present political agenda is the migration crisis. Apart from economic and environmental migration, we experienced in the latest years the exacerbation of some political conflicts and implicitly a political-based migration too. Tragic images of migrants’ attempts to cross the Mediterranean Sea or traversing other migration corridors were doubled by welcomed or hostile reactions of authorities in the countries of destination. The press did not spare us details about the migration routes, infrastructures, migrants’ pack-sacks, clothes and their smart technologies (see, for example, Meyer, 2015).